The Development of An Atomic Structure Module Based on A Scientific Approach with Probing Prompting Questions for Class X SMA/MA - Zuwita, Ariani; Ellizar, Ellizar (Universitas Negeri Padang, 2024)
Curriculum 2013 demands that learning can increase students activeness and thinking skills by emphasing a scientific approach. But in practice the teacher is still constrained to make students active in learning. One of the things can be done is to ask questions in the learning process so that students thinking skill can be improved. The types of questions that can be used are probing and prompting. This research aims to develop teaching materials in the form of modules based on a scientific approach with each stage containing probing and prompting questions on atomic structure material for class X SMA/MA. The type of research used is R&D (Research and Development) with a Plomp development model which has stage is 1) preliminary research, 2) prototyping stage, 3) assasment phase. The modules produced are tested for validity and practicality. The data obtained was processed using the Aiken’s V formula. Based on the results of the research on the validity test of the module on 5 validators, the Aiken scale value was 0,86 in the high category. In the practicality test conducted at SMAN 12 Padang by 2 teachers and 22 students with an Aiken scale score 0,84 and 0,88 in the high category